Development and characterization of GaN high electron mobility transistors for low noise applications - Liu, Zhihong (2011)
This thesis presents the fabrication, detailed characterization and analysis of AlGaN/GaN high electron mobility transistors (HEMTs) and metal-insulator-semiconductor HEMTs (MISHEMTs) for microwave low-noise applications. The major contributions of this thesis are given below: (1) Fabrication processes for conventional Schottky-gate GaN HEMTs and MISHEMTs were developed particularly for low-noise applications. (2) The physical mechanisms of the OFF-state breakdown characteristics were comprehensively studied for GaN HEMTs on Si. (3) The surface passivation effects on the bias-dependent microwave small signal characteristics and noise characteristics have been comprehensively studied for AlGaN/GaN HEMTs on Si. The effects of SiN surface passivation on the bias-dependent small signal equivalent circuit elements have been investigated in detail. (4) The temperature dependent noise performance was characterized for GaN HEMT on high-resistivity Si substrate over a wide temperature range from -50 oC to 200 oC. An analytical model for the temperature dependent microwave noise parameters has been proposed for the GaN HEMTs. (5) A 0.25-um Atomic-Layer-Deposited (ALD) Al2O3/AlGaN/GaN MISHEMT on high-resistivity Si with excellent noise performance was demonstrated. A state-of-the-art minimum noise figure (NFmin) value of 1.0 dB at 10 GHz was achieved for a 0.25 um ALD Al2O3/AlGaN/GaN MISHEMT on Si for the first time. The 2-dimensional-electron-gas (2DEG) density and transport properties in the ALD-Al2O3/AlGaN/GaN MISHEMTs have been studied.